EKSPERIMENTASI MODEL PEMBELAJARAN KOOPERATIF TIPE GROUP INVESTIGATION (GI) DAN JIGSAW II DITINJAU DARI KEMAMPUAN SPASIAL SISWA - Ahmad Ahmad; Budi Usodo; Riyadi Riyadi (Jurnal Tatsqif, 2017)
The objectives of this research were to investigate: (1) which learning model of the Cooperative learning model of the GI type, the Jigsaw IIlearning model, and the direct learning model results in a better learning achievement, (2) which students among the students with the high, moderate, and low spatial abilities have a better learning achievement, (3) in each of the Cooperative learning model of the GI type, the Jigsaw II learning model, and the direct learning which students among the students with the high, moderate, and low spatial abilities have a better learning achievement, and (4) in each of the high, moderate, and low spatial abilities which learning model of the Cooperative learning model of the GI type, the Jigsaw II learning model, and the direct learning model results in a better learning achievement .This research used the quasi experimental research method with the factorial design of 3 3 ?. Its population was all of the students of State Junior Secondary Schools of Karanganyar regency. The samples of the research were taken by using the stratified cluster random samplingtechnique. The samples consisted of 285 students. T he data of the research were gathered through test of spatial ability and test of learning achievement in Mathematics. The proposed hypotheses of the research were analyzed by using the two-way analysis of variance with unbalanced cells. The results of the research are as follows. 1) The cooperative learning model of the GI type results in a better learning achievement than the direct learning model, but results in the same good learning achievement in Mathematics as the Jigsaw II learning model, and the Jigsaw II learning model results in a better learning achievement than the direct learning model. 2). The students with the high spatial ability and those with the moderate spatial ability have a better learning achievement in Mathematics than those with the low spatial ability, but the students with the high spatial ability have the same good learning achievement in Mathematics as those with the moderate spatial ability. (3) in each of the Cooperative learning model of the GI type, the Jigsaw II learning model, and the direct learning, students with the high spatial ability have the same good learning achievement in Mathematics as those with the moderate spatial ability, and both the students with the high spatial ability and those with the moderate spatial ability have a better learning achievement in Mathematics than those with the low spatial ability. 4) in each of the high, moderate, and low spatial abilities, the Cooperative learning model of the GI type and the Jigsaw II learning model result in a better learning achievement in Mathematics than the direct learning model , but the cooperative learning model of the GI type results in the same good learning achievement as the Jigsaw II learning model.